Grey book. Expansionist policy and Neo-Nazism in West Germany. Backgrounds, aims, methods. A documentation (National Council of the National Front, 1967)
Seperate: Albert Norden, Speech at the international press conference of the National Council of the National Front of Democratic Germany on 29 march 1967 in Berlin. 16 p.